P.185 Impact-detecting helmets as indicators of concussion and blood brain barrier integrity in university football players. (November 2021) - Jones, C; Audas, L; Kureshi, N; Kamintsky, L; Fenerty, L; Wilson, L; Atkinson, C; Friedman, A; Clarke, DB
Abstract : Background: Repetitive sub-concussive head impacts have been associated with changes in brain architecture and neurological symptoms. In this study, we examined the association between repetitive sub-concussive impacts, impact burden, and blood brain barrier (BBB) integrity in university football players. Methods: 59 university football players were followed over the 2019 season. Athletes with diagnosed concussion and those sustaining impacts that alerted a sideline impact monitor (relayed by ferroelectric helmet sensors) underwent dynamic contrast-enhanced MRI (DCE-MRI) within one week of injury/alert, and 4 weeks following initial incident. Results: Helmets recorded 2648 impacts over 48 cumulative hours. 8 concussions occurred during the 2019 season (2.82 per 1000 activity hours). On average, athletes with a diagnosed concussion had 55.3 impacts to the front sensor, compared to 14.1 in non-concussed athletes. Athletes who consented to DCE-MRI (n=5) had 10.78% BBB-D within a week of concussion/alert, and 6.77% BBB-D at 4-weeks. Conclusions: We show quantification of BBB integrity relative to head impact burden for the first time. This preliminary study highlights the potential of impact-detecting helmets to provide relevant impact characteristics and offers a foundation for future work on neurological consequences of repetitive sub-concussive impacts.